(untitled) (Bangladesh Journal of Medical Science, 2017)
Choledochal Cyst is a relatively rare condition. Even rarer is a choledochal cyst in association with a gallbladder carcinoma. This study reports a rare case of choledochal cyst coexisting with gallbladder carcinoma in a Bangladeshi patient. A 35 year old lady presented at IBN Sina Medical College Hospital, Kallyanpur, Dhaka with the history of recurrent right upper quadrant abdominal pain from childhood, which became severe for last 4 days before admission. The pain was colicky in nature and radiated to the back. Episodes were associated with low-grade fever, anorexia as well as vomiting. The preoperative diagnosis was made by abdominal ultrasound and MRCP. Exploratory laparotomy, enbloc cholecystectomy with excision of the choledochal cyst and roux-en-Y hepaticojejunostomy was also done. Post operative recovery was uneventful. Patient was followed up for six months and no obvious complication was noticed. Early suspicion of this rare pancreato-billiary disease is important because surgical treatment is the only way to avoid the complications of the disease. Bangladesh Journal of Medical Science Vol.16(4) 2017 p.602-605